2015
DOI: 10.1590/1807-1929/agriambi.v19n12p1203-1208
|View full text |Cite
|
Sign up to set email alerts
|

Modelagem matemática da secagem de espuma de graviola

Abstract: R E S U M OObjetivou-se, com este trabalho, propor e ajustar modelos matemáticos ao processo de secagem de espuma de graviola em diferentes condições de ar, determinar o coeficiente de difusão efetivo e obter a energia de ativação. Para a formação da espuma foi adicionada, à polpa, albumina, na concentração de 7,43% em massa e submetida à agitação em batedeira doméstica, durante 15 min; em seguida, esta foi espalhada sobre bandejas formando uma camada fina de cerca de 5,0 mm de espessura cujas condições de sec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
1
12

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(40 citation statements)
references
References 12 publications
2
24
1
12
Order By: Relevance
“…In the samples containing 8% of albumin ( Figure 2B), there was a reduction of 28.62% of the drying time for the samples to reach the moisture ratio of 0.5. Baptestini et al (2015) subjected soursop pulp mixed with 7.43% of albumin to the temperature range of 40 to 80 ºC and observed that the drying time at 80 ºC was 4.6 times shorter than that for 40 ºC. Madureira et al (2011) observed that the increase of 10 ºC in the temperature for the drying of cactus pear in forced-air oven led to reduction in the drying time.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the samples containing 8% of albumin ( Figure 2B), there was a reduction of 28.62% of the drying time for the samples to reach the moisture ratio of 0.5. Baptestini et al (2015) subjected soursop pulp mixed with 7.43% of albumin to the temperature range of 40 to 80 ºC and observed that the drying time at 80 ºC was 4.6 times shorter than that for 40 ºC. Madureira et al (2011) observed that the increase of 10 ºC in the temperature for the drying of cactus pear in forced-air oven led to reduction in the drying time.…”
Section: Resultsmentioning
confidence: 99%
“…Among the drying processes to obtain fruit pulp powders, foam mat drying stands out. This is a method in which the liquid or semi-liquid food is mixed with foam agents and transformed into a foam through agitation, and then subjected to drying with hot air (Baptestini et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…As temperaturas do ar de secagem selecionadas foram de 50 °C, 55 °C, 60 °C, 65 °C e 70 °C, totalizando cinco níveis de temperatura e perfazendo, portanto, um número adequado para o estudo de um fator quantitativo. Esses valores de temperatura selecionados proporcionam menores alterações de características nutricionais e sensoriais da polpa, sendo este um intervalo comumente utilizado no método de leito em espuma (MEZIANE, 2011;BAPTESTINI et al, 2015). A massa das amostras foi registrada utilizando-se uma balança com resolução de 0,001 g, em intervalos de 15 minutos durante a primeira hora, 30 minutos durante a segunda e terceira hora, e 60 minutos até que a massa permanecesse constante.…”
Section: Experimento Finalunclassified
“…Para todas as temperaturas, a razão de umidade reduziu-se rapidamente no início e, posteriormente, diminuiu lentamente à medida que se aumentou o tempo de secagem. Tais características também foram observadas na operação de secagem de nabo forrageiro (SOUSA et al, 2011) e graviola (BAPTESTINI et al, 2015).…”
Section: Araújo C S Et Alunclassified
See 1 more Smart Citation